Upaya Menunjang Keterampilan Berbicara Bahasa Inggris Anak dengan Permainan Anak Ayam - Firdha Hayati (Ibtida'i, 2022)
This study aims to describe how “chicks games” can be a game to demonstrate children’s speaking skill. In this research, the children are about aged 5-6 years. Qualitative approach is chosen with the research subjects is 20 of 1st graders of Madrasah Ibtidaiyah Al Ashriyah at Banjarmasin. Interviews, observation, and documentation were implemented in this research. While the technique used in data analysis is using interactive models from Miles and Huberman. The stages of data collection from Miles and Huberman are the data reduction stage, the data display stage, and the data analysis conclusion stage. The results of this study state that the teacher provides the opportunity for children to demonstrate English language skills by repetition methods, playing methods and singing methods. These three things are in line with the nature of children where children will more easily grasp learning.